New Constraints on Global Geochemical Cycling During Oceanic Anoxic Event 2 (Late Cretaceous) From a 6‐Million‐year Long Molybdenum‐Isotope Record. (23rd March 2021) - Dickson, Alexander J.; Jenkyns, Hugh C.; Idiz, Erdem; Sweere, Tim C.; Murphy, Melissa J.; van den Boorn, Sander H. J. M.; Ruhl, Micha; Eldrett, James S.; Porcelli, Donald
Abstract: Intervals of extreme warmth are predicted to drive a decrease in the oxygen content of the oceans. This prediction has been tested for the acme of short (<1 million years) episodes of significant marine anoxia in the Phanerozoic geological record known as Oceanic Anoxic Events (OAEs). However, there is a paucity of data spanning prolonged multimillion‐year intervals of geological time before and after OAEs. We present a Mo‐isotope record from limestones and marlstones of the Eagle Ford Group, South Texas, which was deposited in the southern Cretaceous Western Interior Seaway of North America during a 6‐million‐year period encompassing OAE 2 (Late Cenomanian–early Turonian: ∼94 Ma). Mo‐isotope compositions from deposits that formed in euxinic (sulfidic) conditions before OAE 2 allow the paleo‐seawater composition to be constrained to 1.1%–1.9%. This range of values overlaps previous estimates of up to ∼1.5% for the peak of OAE 2 determined from similarly sulfidic sediments deposited in the restricted proto‐North Atlantic Ocean. Mo‐isotopes thus varied by less than a few tenths of per mil across one of the most extreme intervals of global deoxygenation in the Late Phanerozoic. Rather than a limited change in oceanic deoxygenation, we suggest that the new data reflect changes to global iron cycling linked to basalt‐seawater interaction, terrestrial weathering and expanded partially oxygenated shallow shelf‐seas that played a key role in the burial of isotopically light molybdenum, thus acting as a counterbalance to its removal into sulfidic sediments. Plain Language Summary: Ocean deoxygenation is projected to become more pronounced in the future. This environmental change will place stress on marine biota and will alter biogeochemical systems and climate feedbacks. Oceanic Anoxic Events (OAEs) are a rich source of information about marine deoxygenation in the geological past but there are fundamental questions surrounding the true magnitude and pacing of redox change during these events. We demonstrate that the variability in one of the key geochemical tools used to reconstruct past oceanic oxygen declines, molybdenum isotopes, experienced relatively little change across one of the most significant Oceanic Anoxic Events of the Late Phanerozoic. We argue that this limited variability partly reflects geochemical feedbacks that buffered the molybdenum cycle, thereby preventing a major isotope excursion. Key Points: The pre OAE 2 Mo‐isotope composition of seawater constrained to 1.1%–1.9% Limited change in seawater Mo isotopes during OAE 2 linked to enhanced global Mo burial with Fe minerals The response of other redox‐sensitive isotopic systems to major ocean redox changes may be affected by global changes in Fe cycling